Predicting youth reoffending after incarceration: added value of protective factors and heart rate variability - Ruigh, Esther L. de (The journal of forensic psychiatry & psychology, 2021)
This study examined a biopsychosocial approach on risk assessment in a clinical sample of youth offenders. In search of enhancing the validity of prediction of recidivism through risk factors alone, the added value of protective and neurobiological factors was measured. In 209 male youth offenders (age 15-24), risk and protective factors were assessed with the Structured Assessment of Violence in Youth (SAVRY) and the Structured Assessment of Protective Factors for violence risk-Youth Version (SAPROF-YV). Autonomic nervous system (re)activity was assessed, and cortisol and testosterone levels were measured in saliva. Recidivism data were obtained from official criminal records. As expected, risk factors alone provided moderate predictive validity for general and violent recidivism. Incorporating protective factors and Heart Rate Variability (HRV) reactivity significantly improved prediction models. Risk assessment may gain by adopting a broader, biopsychosocial perspective. Including neurobiology and protective factors in risk assessment could improve release decision-making, offer guidance for better tailored interventions, and enhance chances of successful community reintegration.